Research on DC Corona Test of Typical Electrodes and Corona Limited Electric Field Magnitude for Valve Hall Fittings. Issue 1 (February 2021) - Shiling, Zhang; Qiang, Yao
Abstract: In order to prevent the surface corona of valve hall fittings and obtain the corona limited electric field magnitude, the research designed dc corona test of spherical electrode and ring electrode with the different radius of curvature. The electrodes were used to imitate valve tower shield plate, grading ring, grading ball and grading shield for bushing. By the reason that the uneven electric field of irregular conductor can't be calculated theoretically or measured accurately, the three-dimensional finite element model is used for simulating calculation. The variation of typical electrode corona inception electric field is analyzed and threshold value of corona inception electric field of valve hall fittings is acquired. With adequate modification, limited electric field magnitude for the project is proposed. The corona inception electric field magnitude of electrical equipment under the equivalent diameter of 200mm is 2000Vmm −1, and that of electrical equipment with an equivalent diameter of more than 200 mm is 1200 V mm −1 .